2021
DOI: 10.1111/jcmm.16302
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole promotes cisplatin‐induced acute kidney injury via enhancing tubular necroptosis

Abstract: Acute kidney injury (AKI) is the main obstacle that limits the use of cisplatin in cancer treatment. Proton pump inhibitors (PPIs), the most commonly used class of medications for gastrointestinal complications in cancer patients, have been reported to cause adverse renal events. However, the effect of PPIs on cisplatin‐induced AKI remains unclear. Herein, the effect and mechanism of lansoprazole (LPZ), one of the most frequently prescribed PPIs, on cisplatin‐induced AKI were investigated in vivo and in vitro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…A pharmacological suppression of RIPK1 activity ameliorated tubular cell necroptosis and renal injury in cisplatin-treated mice [ 46 , 47 ]. Previous studies have reported that the renal expression of RIPK1, RIPK3, and p-MLKL was increased after cisplatin treatment [ 48 , 49 ]. Interestingly, these changes were significantly attenuated by 6-shogaol.…”
Section: Discussionmentioning
confidence: 99%
“…A pharmacological suppression of RIPK1 activity ameliorated tubular cell necroptosis and renal injury in cisplatin-treated mice [ 46 , 47 ]. Previous studies have reported that the renal expression of RIPK1, RIPK3, and p-MLKL was increased after cisplatin treatment [ 48 , 49 ]. Interestingly, these changes were significantly attenuated by 6-shogaol.…”
Section: Discussionmentioning
confidence: 99%
“…However, findings from experimental models and systems are contradictory. For example, omeprazole induced tubular cell death in healthy mice in vivo 216 and another PPI, lansoprazole, increased the severity of experimental cisplatin-induced AKI 217 . By contrast, one in vitro study found that omeprazole could scavenge lipid peroxyl radicals, and demonstrated short-term (48 h) anti-ferroptotic effects in cultured cells following cystine deprivation; however, omeprazole was toxic at higher doses 218 .…”
Section: Towards Clinical Implementationmentioning
confidence: 99%
“…Subsequently, the sections were stained with hematoxylin–eosin (HE) and periodic acid‐Schiff (PAS), and observed by light microscopy (Zeiss, Germany). Tubular cell necrosis, loss of brush border, cast formation, and tubule dilation were scored 0–4 as a percentage of the whole cortical area of the kidney slices:1, <10% damage; 2, 10%–25% damage; 3, 26%–75% damage; 4, >75% damage 33 …”
Section: Methodsmentioning
confidence: 99%
“…Tubular cell necrosis, loss of brush border, cast formation, and tubule dilation were scored 0-4 as a percentage of the whole cortical area of the kidney slices:1, <10% damage; 2, 10%-25% damage; 3, 26%-75% damage; 4, >75% damage. 33 For immunohistochemistry (IHC) staining, after quenching with endogenous peroxidase, achieving antigen retrieval, and blocking nonspecific binding sites, the sections were incubated with primary antibodies, including anti-UQCRC2 (Abclonal, Cat. No.…”
Section: Histopathology and Immunohistochemistrymentioning
confidence: 99%